2022
DOI: 10.1155/2022/7258152
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin Levels and the Risk of Myopenia and Rheumatoid Cachexia in Women with Rheumatoid Arthritis

Abstract: Background. Myostatin is a regulator of muscle size. To date, there have been no published studies focusing on the relation between myostin levels and myopenia in rheumatoid arthritis (RA). Objective. Evaluate the value of serum myostatin as a biomarker of cachexia and low skeletal muscle mass (LSMM) in RA patients, along with whether high serum myostatin is associated to these conditions after adjusting for potential confounders. Methods. This cross-sectional study included 161 female RA patients and 72 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…We were unable to evaluate the effect of the lack of treatment with DMARDs because all our patients received these drugs and only a very small proportion of RA patients were not compliant to the prescription. Our findings that the lack of a response to combined therapy with csDMARDs is a risk factor of muscle wasting in RA, is consistent with the evidence that persistent inflammatory disease activity, a decrease in physical performance, and the overexpression of pro-inflammatory cytokines, adipokines, and other molecules increase muscle degradation and can lead to the development of low muscle mass in these patients [ 5 , 14 , 29 ]. We consider our findings that a repetitive failure of combined treatment with csDMARDs is associated with a greater risk of muscle wasting in RA women to be relevant for clinical care in RA patients.…”
Section: Discussionsupporting
confidence: 88%
“…We were unable to evaluate the effect of the lack of treatment with DMARDs because all our patients received these drugs and only a very small proportion of RA patients were not compliant to the prescription. Our findings that the lack of a response to combined therapy with csDMARDs is a risk factor of muscle wasting in RA, is consistent with the evidence that persistent inflammatory disease activity, a decrease in physical performance, and the overexpression of pro-inflammatory cytokines, adipokines, and other molecules increase muscle degradation and can lead to the development of low muscle mass in these patients [ 5 , 14 , 29 ]. We consider our findings that a repetitive failure of combined treatment with csDMARDs is associated with a greater risk of muscle wasting in RA women to be relevant for clinical care in RA patients.…”
Section: Discussionsupporting
confidence: 88%
“…Meanwhile, a study performed by Gonzalez-Ponce et al in Mexico evaluated 161 women with RA and compared their serum myostatin levels (obtained using enzyme-linked immunoassay) with 72 women without rheumatic disease (but including those with high blood pressure and diabetes mellitus type II). This study, similarly, found higher serum myostatin levels in the RA group (11.89 (1.2–140) ng/mL) than in the control group (7.9 (1.2–19.6) ng/mL) [ 63 ] ( Table 2 ).…”
Section: Myostatin In Rheumatoid Arthritismentioning
confidence: 70%
“…In the study performed by Murillo-Saich et al [ 61 ], they found an inverse correlation between myostatin serum levels, skeletal muscle mass index, and free fat mass index, while, in the study by Gonzalez-Ponce et al [ 63 ], the group of RA patients with low muscle mass also had higher levels of myostatin, as well as a greater frequency of patients with high levels of myostatin. Both studies agree with the hypothesis since myostatin is a negative regulator of muscle growth [ 61 , 63 ].…”
Section: Myostatin In Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Potential explanatory factors for accelerated decline in LTM may be, but are not restricted to, the inflammatory burden and dysregulation of myokines such as myostatin. 35 , 36 Further studies are required to fully assess the diagnostic and prognostic value of body composition in patients with IIM.…”
Section: The Metabolic and Bioenergetic Disturbances In Skeletal Musc...mentioning
confidence: 99%